Comparison of the diets of breeding royal (Eudyptes schlegeli) and rockhopper (Eudyptes chrysocome) penguins on Macquarie Island over three years - Hull, CL (1999)
A 3 year study of the diets of breeding royal Eudyptes schlegeli and rockhopper E. chrysocome penguins was carried out at two nearby colonies on Macquarie Island. Diets of both species were dominated by euphausiids and myctophid fish, in particular Euphausia vallentini and Krefftichthys anderssoni. Prey items were those found in the region of the Polar Frontal Zone, confirming the importance of this zone to these penguins. Diets of both species before hatching of the chicks were variable between years, and differences in quantity of food brought ashore and degree of digestion of prey suggested inter-annual variation in distribution of prey resources. No dietary differences were detected in either penguin species across the breeding season, which reflected variability in diet at all stages, indicating that individual penguins foraged in separate areas. Significant differences between the two species were found, royal penguins consuming more myctophid fish and rockhopper penguins consuming more euphausiids. Differences were also found in the size class of prey items taken and the degree of digestion of food by both penguin species, indicating that prey were taken from different sectors of the ocean. It is concluded that the overlap in diet is small in individuals from these two spatially close colonies and, contrary to previous studies, indicates a separation in the resources used by both species. The contrast with previous studies is most likely a reflection of the different methods used to assess overlap and, to a lesser extent, the years and colonies in which the comparisons were made.